Natural food additives, ingredients and flavourings - Baines, David; Seal, Richard (Food technologist); ScienceDirect eBooks (Oxford ; Philadelphia : Woodhead Publishing, 2012)
As the links between health and food additives come under increasing scrutiny, there is a growing demand for food containing natural rather than synthetic additives and ingredients. Natural food additives, ingredients and flavourings reviews the legislative issues relating to natural food additives and ingredients, the range of natural food additives and ingredients, and their applications in different product sectors. After an exploration of what the term 'natural' means in the context of food ingredients, part one focuses on natural food colourings, low-calorie sweeteners and flavour enhancers, followed by a consideration of natural antioxidants and antimicrobials as food ingredients. The book goes on to review clean label starches and proteins, the application of natural hydrocolloids as well as natural aroma chemicals and flavourings from biotechnology and green chemistry. Part two considers specific applications in different products. Natural ingredients in savoury food products, baked goods and alcoholic drinks are examined, as are natural plant extracts in soft drinks and milk-based food ingredients. With is distinguished editors and expert team of international contributors, Natural food additives, ingredients and flavourings is an invaluable reference tool for all those involved in the development and production of foods with fewer synthetic additives and ingredients. Reviews the legislative issues relating to natural food additives and ingredients, the range of natural food additives and ingredients, and their applications in different product sectorsExplores what the term 'natural' means in the context of food ingredients, focusses on natural food colourings, low-calorie sweeteners and flavour enhancers, and considers natural antioxidants and antimicrobials as food ingredientsExamines natural ingredients in savoury food products, baked goods and alcoholic drinks, natural plant extracts in soft drinks and milk-based food ingredients.
7.4 Amylose and amylopectin7.5 Starch: extraction and manufacture; 7.6 Starches from different sources; 7.7 Modification of starches; 7.8 Clean label starches; 7.9 Conclusions and future trends; 7.10 Sources of further information and advice; 7.11 References; 8 The application of natural hydrocolloids to foods and beverages; 8.1 Introduction; 8.2 The main types of hydrocolloids used in foods and beverages; 8.3 Natural hydrocolloids: their manufacture, properties and applications; 8.4 Future trends; 8.5 Sources of further information and advice; 8.6 References.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Food additives; Food additives -- Analysis; TECHNOLOGY & ENGINEERING -- Food Science; Food additives; Food additives -- Analysis; Electronic books